Sistem Pengurusan Kedai Basikal Budget & Customized: Sistem Pengurusan Kedai Basikal Budget & Customized - Alias, Muhammad Aiman; Saringat, Mohd Zainuri; Nita Sophia Abd Hamid (Applied Information Technology And Computer Science, 2024)
The Budget & Customized Bicycle Shop Management System (SPKBBC) is a web-based system developed to improve the management method of the Budget & Customized Bicycle Shop in addition to being able to expand the business of bicycles, accessories and components. The development of this system aims to replace the method written sales records with digital data storage to ensure systematic records. This system can also make it easier for customers to buy bicycles and products easily through the customer’s laptop. The Evolution Prototype model used as a guide in developing this system and the programming languages ​​HTML, CSS and JavaScript used for the front-end, while MySQL and PHP are used for the database. Finally, the SPKBBC is expected to benefit manager to increase efficiency in managing bicycle shop easily and effectively using laptops with Internet access.